Hasidism reappraised - Weiss, J. G. (Joseph George), 1918-1969; Rapoport-Albert, Ada (Littman library of Jewish civilization (Series), 1996)
Hasidism has been a seminal force and source of controversy in the Jewish world since its inception in the second half of the eighteenth century. This book, the first comprehensive critical study of this intriguing movement in English, offers a wide-ranging treatment of the subject in all its aspects by what is effectively the entire present generation of scholars working in the field. With contributions ranging from the history of theology and ideas through social and economic history to sociology, Hasidism Reappraised encompasses a complete field of contemporary scholarship in a discipline that is central to our understanding of modern Jewish history and the contemporary Jewish world.